Exome sequencing in sporadic autism spectrum disorders identifies severe de novo mutations - O'Roak, B; Deriziotis, P; Lee, C; Vives, L; Schwartz, J; Girirajan, S; Karakoc, E; MacKenzie, A; Ng, S; Baker, C; Rieder, M; Nickerson, D; et al. (2011)
Evidence for the etiology of autism spectrum disorders (ASDs) has consistently pointed to a strong genetic component complicated by substantial locus heterogeneity. We sequenced the exomes of 20 individuals with sporadic ASD (cases) and their parents, reasoning that these families would be enriched for de novo mutations of major effect. We identified 21 de novo mutations, 11 of which were protein altering. Protein-altering mutations were significantly enriched for changes at highly conserved residues. We identified potentially causative de novo events in 4 out of 20 probands, particularly among more severely affected individuals, in FOXP1, GRIN2B, SCN1A and LAMC3. In the FOXP1 mutation carrier, we also observed a rare inherited CNTNAP2 missense variant, and we provide functional support for a multi-hit model for disease risk. Our results show that trio-based exome sequencing is a powerful approach for identifying new candidate genes for ASDs and suggest that de novo mutations may contribute substantially to the genetic etiology of ASDs. © 2011 Nature America, Inc. All rights reserved.